A Nexus Approach for the MENA Region—From Concept to Knowledge to Action - Hoff, Holger; Alrahaife, Sajed Aqel; El Hajj, Rana; Lohr, Kerstin; Mengoub, Fatima Ezzahra; Farajalla, Nadim; Fritzsche, Kerstin; Jobbins, Guy; Özerol, Gül; Schultz, Robert; Ulrich, Anne (Frontiers in Environmental Science, 2019)
There is wide agreement that a nexus or integrated approach to managing and governing natural resources such as land, water, and energy can improve environmental, climate, human, and political security. However, few if any countries in the MENA region have made progress in implementing such an approach. There appear to be several constraints inhibiting the development and adoption of nexus approaches. These constraints include strong sectoral silos, insufficient incentives for integrated planning and policy making at all levels, and limited vision, knowledge, and practical experience to guide successful implementation. In turn, the limited implementation and hence lack of empirical evidence of a nexus approach, which could demonstrate its benefits, does little to strengthen political will for the development of adequate incentives, structures, and procedures. Against this backdrop, this paper presents five case studies which take an integrated approach, in three MENA countries, namely Jordan, Lebanon, and Morocco. Based on an analytical framework developed here, the paper analyses and compares the success factors for nexus implementation, and also for transfer and upscaling. The analysis emphasizes the need for appropriate framework conditions, targeted investments and pioneering actors, to make integrated approaches across sectors and levels work. With the evidence presented, the paper aims to set in motion a positive or virtuous cycle of generating more nexus evidence, improved framework conditions, further nexus implementation on the ground, and from that even more nexus evidence. Finally, the paper contributes to overcoming the repeated requests for better definition and conceptualization of the nexus, which often has slowed down adoption of the concept.